Transform Sustainable: Innovating for a Sustainable Future - Joyce Caroline Areas Pereira; Leonardo Silva Manso (Universitas Diponegoro, 2024)
The Transform Sustainable Program of the Federal Institute of Education, Science and Technology of the South of Minas Gerais (IFSULDEMINAS) is an example of how creativity and innovation can transform challenges into solutions. Through the transformation of donated and seized materials into high-value products, the program contributes to environmental protection, income generation and social development. The program's main focus is on sustainability, reducing material disposal, promoting reuse and recycling, and contributing to the circular economy. Technological innovation is also fundamental, with the development of innovative solutions to transform discarded materials into high-value products. The program has a partnership with several institutions, such as the Brazilian Federal Revenue Service (RFB), city halls, schools and NGOs, demonstrating the power of collaboration to generate positive social impact. By generating income for local communities, promoting environmental education and social development, the program contributes to building a fairer and more prosperous future for everyone. Transform Sustainable is an inspiring model that demonstrates the potential of sustainability, innovation and collaboration to build a greener, fairer and more prosperous future for all. Through the union of efforts between IFSULDEMINAS and several institutions, the program is transforming the present and building a more sustainable future for the next generations.